1994
DOI: 10.1007/bf01839225
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chromosome-sized DNA and genome typing of isolated strains ofTaylorella equigenitalis

Abstract: Analysis of chromosome-sized DNA and genome typing of Taylorella equigenitalis NCTC11184, Kentucky 188, and five strains of T. equigenitalis isolated in Japan were carried out. The three restriction enzymes used, ApaI, NaeI and NotI, cleaved the genomic DNAs of five Japanese strains of T. equigenitalis into relatively limited numbers of restriction fragments, which were well resolved on crossed-field gel electrophoresis (CFGE). The respective profiles after CFGE of the restriction fragments from all five strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Our previous ¢nding clearly demonstrated that pulsed-¢eld gel electrophoresis (PFGE) pro¢les after separate digestion with ApaI and NotI of the genomic DNAs from these three strains of T. equigenitalis, namely NCTC11184 T , Kentucky188 and EQ59, were distinctly di¡erent from each other (Matsuda et al, 1994(Matsuda et al, , 1999(Matsuda et al, , 2000Kagawa et al, 2001) and con¢rmed that heterogeneous genotypes of T. equigenitalis have a global distribution . In particular, the distinct genotypes between the strain NCTC11184 T and Kentucky188 were clearly demonstrated by the PFGE pro¢les as described previously (Matsuda et al, 1998(Matsuda et al, , 2000.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous ¢nding clearly demonstrated that pulsed-¢eld gel electrophoresis (PFGE) pro¢les after separate digestion with ApaI and NotI of the genomic DNAs from these three strains of T. equigenitalis, namely NCTC11184 T , Kentucky188 and EQ59, were distinctly di¡erent from each other (Matsuda et al, 1994(Matsuda et al, , 1999(Matsuda et al, , 2000Kagawa et al, 2001) and con¢rmed that heterogeneous genotypes of T. equigenitalis have a global distribution . In particular, the distinct genotypes between the strain NCTC11184 T and Kentucky188 were clearly demonstrated by the PFGE pro¢les as described previously (Matsuda et al, 1998(Matsuda et al, , 2000.…”
Section: Discussionmentioning
confidence: 93%
“…Preparation of agarose blocks from these cell suspensions and techniques for PFGE were performed as previously described (7,14,16). Genomic DNA was digested via restriction enzymes ApaI, NotI, and NaeI.…”
Section: Methodsmentioning
confidence: 99%
“…The breeding of thoroughbreds in Japan and the absence of serological differences among tested strains of T. equigenitalis have also been described previously (MIYAZAWA et al 1995). The culture of strains, the preparation of agarose blocks and the procedure for PFGE after digestion with ApaI and with NotI, as well as the reasons for the choice of these restriction enzymes, have also been described in detail (MATSUDA et al 1994, MIYAZAWA et al 1995.…”
Section: Methodsmentioning
confidence: 99%